The economy of medieval Hungary - Laszlovszky, József; Nagy, Balázs; Szabó, Péter; Vadas, András (2018)
Introduction: Hungarian medieval economic history : sources, research and methodology / Jozsef Laszlovszky, Balazs Nagy, Peter Szabo and Andras Vadas – Structure – Long-term environmental changes in medieval Hungary : changes in settlement areas and their potential drivers / Laszlo Ferenczi, Jozsef Laszlovszky, Zsolt Pinke, Peter Szabo and Andras Vadas – Demographic issues in late medieval Hungary : population, ethnic groups, economic activity / Andras Kubinyi and Jozsef Laszlovszky – Mobility, roads and bridges in medieval Hungary / Magdolna Szilagyi – Human-nature interaction in production – Agriculture in medieval Hungary / Jozsef Laszlovszky – Animal exploitation in medieval Hungary / Laszlo Bartosiewicz, Anna Zsofia Biller, Peter Csippan, Laszlo Daroczi-Szabo, Marta Daroczi-Szabo, Erika Gal, Istvan Kovats, Kyra Lyublyanovics and Eva Agnes Nyerges – Mining in medieval Hungary / Zoltan Batizi – Salt mining and trade in Hungary before the Mongol invasion / Beatrix F. Romhanyi – Salt mining and the salt trade in medieval Hungary from the mid-thirteenth century until the end of the middle ages / Istvan Draskoczy – The extent and management of woodland in medieval Hungary / Peter Szabo – Water management in medieval Hungary / Laszlo Ferenczi – Money, incomes and management – Royal revenues in the Arpadian age / Boglarka Weisz – Seigneurial dues and taxation principles in late medieval Hungary / Arpad Nogrady – Minting, financial administration and coin circulation in Hungary in the arpadian and Angevin periods (1000-1387) / Csaba Toth – Coinage and financial administration in late medieval Hungary (1387-1526) / Marton Gyongyossy – Spheres of production – The ecclesiastic economy in medieval Hungary / Beatrix F. Romhanyi – The urban economy in medieval Hungary / Katalin Szende – The medieval market town and its economy / Istvan Petrovics – Crafts in medieval Hungary / Laszlo Szende – The economy of castle estates in the late medieval kingdom of Hungary / Istvan Kenyeres – Trade relations – Domestic trade in the arpadian age / Boglarka Weisz – Professional merchants and the institutions of trade : domestic trade in late medieval Hungary / Andras Kubinyi – Import objects as sources of the economic history of medieval Hungary / Istvan Feld – Foreign trade of medieval Hungary / Balazs Nagy – Foreign business interests in Hungary in the middle ages / Krisztina Arany – Appendix – List of references – Index of geographic names – Index of personal names